2007
DOI: 10.1177/1741143207075387
|View full text |Cite
|
Sign up to set email alerts
|

Leading a Community of Learners

Abstract: This article attempts to provide a foundational understanding of school learning as moral activity as well as intellectual activity. It first develops a distinction between general ethics and professional ethics, and provides an initial explanation of the moral good involved in learning. The moral good of learning is then connected to the fundamental moral agenda of learners, namely, to find, own and engage their true, authentic selves. The article takes up the distortion of the learning process in schools due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 5 publications
0
31
0
1
Order By: Relevance
“…This led them to question the nature of schooling and the interpersonal relationships constructed through it by teachers and students in particular policy contexts. This illustrates how schools become sites in which central, local and institutional policy discourses (Riley & Docking, 2002) and cultures intersect with individual contested values, potentially giving participants the opportunity to construct vibrant communities of learners (Starratt, 2007) reflecting on professional practice (Schon, 1987) in order to develop them (Muijs et al, 2005). Such dialogues help people to question, to modify, as well as to reaffirm their identities (Kearney, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led them to question the nature of schooling and the interpersonal relationships constructed through it by teachers and students in particular policy contexts. This illustrates how schools become sites in which central, local and institutional policy discourses (Riley & Docking, 2002) and cultures intersect with individual contested values, potentially giving participants the opportunity to construct vibrant communities of learners (Starratt, 2007) reflecting on professional practice (Schon, 1987) in order to develop them (Muijs et al, 2005). Such dialogues help people to question, to modify, as well as to reaffirm their identities (Kearney, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Schools are sites in which different macro and local policy perspectives intersect to create micro educational policies and practices (Riley & Docking, 2002) that reflect the particular but contested values of their participants and stakeholders (Begley, 1999), and through which contestation participants and stakeholders can construct dynamic communities of learners (Starratt, 2007). This has led some authors to argue cautiously that teachers may develop particular nationally identifiable approaches to teaching (Givvin et al, 2005) through their 'apprenticeship' as students in their country's schools.…”
Section: Understanding Citizenship Education In National and Europeanmentioning
confidence: 99%
“…Schools are sites in which national policies and local perspectives intersect as people struggle to construct implementable educational policies and practices (Grace, 1995;Riley & Docking, 2002) that reflect particular but contested values (Starratt, 2007). The importance of schools and schooling in shaping social constructions, such as society's views on identity, pluralism and social cohesion, has been increasingly acknowledged by both national governments within Europe and by the EU.…”
Section: Introductionmentioning
confidence: 99%
“…Staratt (2007) described an ethical leader as one who embraces the idea of ethical behavior by "treating everyone in the school with care and compassion, treating them as citizens with rights and responsibilities in the pursuit of the common good and engaging them in the core work of the school, namely authentic teaching and learning" (p 131). Leithwood & Riehl (2003) suggested that ethical leaders shape the culture of the school that includes shared norms, beliefs, values, and an attitude of caring and respect for everyone.…”
Section: )mentioning
confidence: 99%
“…Leithwood and Riehl (2003) As discussed in the Standard 5 section, the principal must communicate and share his vision for the school with all of the shareholders in the community: service clubs, government agencies, mental and health agencies, the school board, business leaders, and state and federal agencies (Leithwood & Riehl, 2003;Staratt, 2007). From all of these groups, a principal can take the pulse of the community and gauge its expectations for the school, as well as find help for students in need.…”
mentioning
confidence: 99%